1975
DOI: 10.1104/pp.56.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Softening and Ethylene Synthesis in Bartlett Pears by 3-Methylene Oxindole

Abstract: A purified preparation of 3-methylene oxindole (3-MeOx) was applied to Bartlett pears (Lyrus communis) by vacuum infiltration. The infiltrated fruit were kept at room temperature at atmospheric or at one-twentieth of an atmospheric tension. The rate of softening was markedly enhanced by the application of 0.1 and 1 ,uM 3-MeOx. At 10 AM 3-MeOx the promotive effect of the compound was diminished. All the employed concentrations of 3-MeOx exceeded the effect of applied ethylene. The enhancement of softening in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…As the auxin activity drops in the explants, the activity of the inhibitor increases, A similar situation was observed in lentil roots (Gaspar, 1973) where tlie so-called inhibitor-/3 fraction was shown to contain at least methyleneoxitidole (Gaspar, Bouchet & Fries, 1972), the well-known oxidation product of IAA, Althougli ABA has been identified in the same fraction (Goldschmidt et al,, 1973), experiments are now being undertaken to clarify whetlier metliyleneoxindole is also present in tliis citrus fraction, Metliyleneoxindole has been proposed by Frenkel et al, (1975) to be involved in the control of ethylene biosynthesis. It is proposed as a working hypothesis tliat, in addition to tlie possible role of ABA in abscission, the decrease in auxin content in the second phase could be related to an endogenous ethylene formation induced by methyleneoxindole.…”
Section: Discussionmentioning
confidence: 68%
“…As the auxin activity drops in the explants, the activity of the inhibitor increases, A similar situation was observed in lentil roots (Gaspar, 1973) where tlie so-called inhibitor-/3 fraction was shown to contain at least methyleneoxitidole (Gaspar, Bouchet & Fries, 1972), the well-known oxidation product of IAA, Althougli ABA has been identified in the same fraction (Goldschmidt et al,, 1973), experiments are now being undertaken to clarify whetlier metliyleneoxindole is also present in tliis citrus fraction, Metliyleneoxindole has been proposed by Frenkel et al, (1975) to be involved in the control of ethylene biosynthesis. It is proposed as a working hypothesis tliat, in addition to tlie possible role of ABA in abscission, the decrease in auxin content in the second phase could be related to an endogenous ethylene formation induced by methyleneoxindole.…”
Section: Discussionmentioning
confidence: 68%
“…This results in the formation of IAA oxidation products which can promote senescence in fruit (6,11). The metabolism of this hormone may be an important factor in the regulation of senescence, and could account for some of the effects brought about by peroxides.…”
Section: Resultsmentioning
confidence: 99%
“…If oxidative degradation of IAA was associated with the onset of ethylene evolution and ripening fruit tissues as proposed by Frenkel and his co-workers (7,8) …”
Section: Resultsmentioning
confidence: 99%
“…However, in pear fruits Frenkel et al (7,8) have reported that it is the IAA oxidation products, but not IAA, which initiate ethylene production and ripening. The regulatory mechanism for the initiation of ethylene production in ripening fruit tissue is known to be different from that in vegetative tissue (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation